PEMBELAJARAN KARAKTER DALAM PENDIDIKAN JASMANI: SUBSTANSI YANG TERABAIKAN - Ali Maksum (Ordik, 2010)
Characters is one of the substance of physical education and sport at school. Unfortunately, until now the practice of learning by teachers is far from adequate. This research aims to uncover the root causes that include pedagogical competence of teachers in teaching character, understanding of teachers about the character, and learning practices of teachers over the years. The research uses a combination of qualitative and quantitative methods. The subjects were 55 physical education teacher, at elementary, junior and high school in Surabaya. The results showed that only 4% of lesson plan of teacher charged consistently characters ranging from the purpose, process, and evaluation. Understanding teachers on character education is relatively narrow, the character is understood more as a courtesy. Another thing that is found in this study is the practice of teaching is teacher-passive internalization, have not lead to constructive-active.